Ab externo device for the treatment of glaucoma: direct flow from the anterior chamber to the ocular surface. Issue 7 (July 2020) - Schultz, Tim; Schojai, Merita; Kersten-Gomez, Inga; Matthias, Elling; Boecker, Joerg; Dick, H. Burkhard
Abstract : A new microinvasive glaucoma surgery device, the Beacon Aqueous Microshunt (BAM), drains aqueous humor directly from the anterior chamber to the surface of the eye vs draining to enclosed spaces within the eye, where outflow resistance, including the episcleral venous pressure, might limit drainage effectiveness. The BAM has a 0.030 mm × 0.048 mm channel and provides a fixed resistance. For implantation, a 1.40 mm wide transcorneal incision into the anterior chamber was created with a posterolimbal outer placement under topical anesthesia. The surgery was easy to execute and had a flat learning curve. Preliminary and early experience have shown success with lowering intraocular pressure immediately postoperatively. In conclusion, the BAM offers a promising minimally invasive surgical procedure.